Metformin and Risks of Aortic Aneurysm and Aortic Dissection: A Mendelian Randomization Study - Lei Wang; Ziyan Lin; Yuzuo Lin; Qingtong Wu; Guodong Zhong; Liangwan Chen (Reviews in Cardiovascular Medicine)
Background: Previous research has suggested that metformin may inhibit the dilation of an abdominal aortic aneurysm (AAA); however, these findings are controversial. Additionally, limited reporting exists on the relationships between metformin and thoracic aortic aneurysm (TAA) and aortic dissection (AD). Therefore, this study aimed to assess the potential relationship between metformin and the risk of aortic aneurysm (AA)/AD using the Mendelian randomization (MR) analysis. Methods: Genome-wide association studies and FinnGen summary data were utilized for the MR analysis. The causal relationship between metformin and AA/AD was primarily assessed using the inverse-variance weighted (IVW) method. Sensitivity analyses were conducted to detect heterogeneity and pleiotropy. Results: The results indicated a negative correlation between metformin treatment and the risk of both AA and AD, with odds ratios(ORs) reported as follows: OR = 0.010, 95% confidence interval (CI):0.000–0.212, p = 0.003 for AA, OR = 0.004, 95% CI: 0.000–0.220, p = 0.007 for abdominal aortic aneurysm (AAA); OR = 0.017, 95% CI: 0.000–0.815, p = 0.039 for thoracic aortic aneurysm (TAA); and OR = 0.001, 95% CI: 0.000–0.531, p = 0.032 for AD using the IVW method. These findings suggested that metformin might act as a protective factor against the occurrence of AA/AD. Furthermore, sensitivity analyses validated the robustness of these findings. Conclusions: This MR analysis identified a potential genetic causal relationship between metformin use and the risks of AA/AD, suggesting that metformin could serve as a protective agent in decreasing the incidences of these conditions.